2022
DOI: 10.1186/s12889-022-13396-2
|View full text |Cite
|
Sign up to set email alerts
|

Supporting and enabling health research in a local authority (SERLA): an exploratory study

Abstract: Background The use of research evidence to underpin public health practice and policy decisions in local government is strongly promoted but its implementation has not been straightforward. This study aimed to explore the factors, relationships and processes that contribute towards accessing, using, and generating research evidence that is relevant to local authority public health and social care and shapes its practice. Methods Semi-structured ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
(34 reference statements)
2
5
0
Order By: Relevance
“…However, attempts to use behavioural science were reported to have increased since the COVID-19 pandemic. This supports previous qualitative work (38,63) which reported that public health teams' desire to use behavioural science and wider research evidence within their practice had increased significantly since the beginning of the pandemic. This increased interest is thought to be due to the greater value placed on scientific evidence during this time (63).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, attempts to use behavioural science were reported to have increased since the COVID-19 pandemic. This supports previous qualitative work (38,63) which reported that public health teams' desire to use behavioural science and wider research evidence within their practice had increased significantly since the beginning of the pandemic. This increased interest is thought to be due to the greater value placed on scientific evidence during this time (63).…”
Section: Discussionsupporting
confidence: 87%
“…Participants felt that this theory-practice gap could be bridged through the use of contextualised examples, such as case studies, and via the provision of training, guidance tools, checklists and in-house expert support. The need for tools and support to guide the implementation of new knowledge into practice and build capacity has been identified as a facilitator across health systems and local authorities ( 44 , 63 , 67 71 ), and was outlined as a key priority within the national strategy produced by PHE and partners ( 8 ). In-house expert support and collaborative partnerships with universities have also been recommended by the Local Government Association ( 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, attempts to use behavioural science were reported to have increased since the Covid-19 pandemic. This supports previous qualitative work (35,60) which reported that public health teams' desire to use behavioural science and wider research evidence within their practice had increased significantly since the beginning of the pandemic. This increased interest is thought to be due to the greater value placed on scientific evidence during this time (60).…”
Section: Checklists To Guide Practicesupporting
confidence: 86%
“…Participants felt that this theory-practice gap could be bridged through the use of contextualised examples, such as case studies, and via the provision of training, guidance tools, checklists and inhouse expert support. The need for tools and support to guide the implementation of new knowledge into practice and build capacity has been identified as a facilitator across health systems and local authorities (40,60,(64)(65)(66)(67)(68), and was outlined as a key priority within the national strategy produced by PHE and partners (8). In-house expert support and collaborative partnerships with universities have also been recommended by the Local Government Association (69).…”
Section: Checklists To Guide Practicementioning
confidence: 99%
“…Establishing a strong governance process to underpin the responsiveness and accountability of the unit was key. As described in other jurisdictions, creating strategic roles within government to embed research within and across teams builds capacity for the use of evidence to better inform actions 25. Embedding the CIU within NSW Health structures (with a direct reporting line to the health secretary/incident controller), rather than outsourcing to an academic unit, may have contributed to its success.…”
Section: Impactmentioning
confidence: 99%